2009
DOI: 10.1177/0278364909345289
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanically Optimized Distributed Tactile Transducer Based on Lateral Skin Deformation

Abstract: This paper presents a tactile transducer device that is optimized from biomechanical data and has a compact, yet modular design. The tactile transducer comprises a 6 × 10 piezo bimorph actuator array with a spatial resolution of 1.8 × 1.2 millimeters and a wide temporal bandwidth. The actuator mounting method was improved from a conventional cantilever method to a dual-pinned method, giving the actuator the capability of maximally deforming glabrous skin for laterotactile stimulation. The results were validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Evidence that our display produces stimuli perceptually similar to real objects was provided in ref. [7], where it was shown that subjects could judge of the orientation of slanted lines with an accuracy better than 10 degrees, which is in line with known thresholds in humans [1]. Moreover, the display readily produces phenomena such as tactile apparent motion [2].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Evidence that our display produces stimuli perceptually similar to real objects was provided in ref. [7], where it was shown that subjects could judge of the orientation of slanted lines with an accuracy better than 10 degrees, which is in line with known thresholds in humans [1]. Moreover, the display readily produces phenomena such as tactile apparent motion [2].…”
Section: Resultssupporting
confidence: 66%
“…We used a tactile display called the Latero (Tactile Labs, tactilelabs.com) that operates by deforming the fingerpad skin with an array of laterally moving pins actuated by miniature piezoelectric bending motors [7]. The display consists of an 8 × 8 array of independent pins within an area of about 1 cm 2 -see Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The tactile stimulus was produced using a Latero Tactile Display (Tactile Labs) (57). This display has an area of 1.2 cm 2 and consists of 8 × 8 pins that can be moved independently in one direction parallel to the surface, with a maximum amplitude of about 0.1 mm and bandwidth of about 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…These devices are usually made of an array of transducer able to deform locally the skin of the fingertip. Basically two tyoe of working principle can be employed: the normal indentation as described in (Wagner et al, 2004) or lateral deformation (Wang & Hayward, 2010). -Tactile Displays or Surface Properties Displays.…”
Section: Wherementioning
confidence: 99%